2020
DOI: 10.1002/jbm4.10397
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Represses CYP2R1, the Vitamin D 25‐Hydroxylase, in the Liver and Extrahepatic Tissues

Abstract: Low plasma level of 25-hydroxyvitamin D (25-OH-D), namely vitamin D deficiency, is associated with obesity and weight loss improves 25-OH-D status. However, the mechanism behind obesity-induced vitamin D deficiency remains unclear. Here, we report that obesity suppresses the expression of cytochrome P450 (CYP) 2R1, the main vitamin D 25-hydroxylase, in both mice and humans. In humans, weight loss induced by gastric bypass surgery increased the expression of CYP2R1 in the s.c. adipose tissue suggesting recovery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 43 publications
4
24
0
2
Order By: Relevance
“…In particular, it has been demonstrated that high fat diet-induced obesity decreased the hepatic gene expression of 25-hydroxylases in mice ( 140 , 141 ). Similar data were found in obese subjects, in whom the overweight determined a decreased expression of cytochrome P450 (CYP) 2R1, the main vitamin D 25-hydroxylase, while the weight loss, induced by gastric bypass, increased the expression of CYP 2R1 ( 142 ).…”
Section: Ir a Determinant Of Deficit Of Vitamin Dsupporting
confidence: 61%
“…In particular, it has been demonstrated that high fat diet-induced obesity decreased the hepatic gene expression of 25-hydroxylases in mice ( 140 , 141 ). Similar data were found in obese subjects, in whom the overweight determined a decreased expression of cytochrome P450 (CYP) 2R1, the main vitamin D 25-hydroxylase, while the weight loss, induced by gastric bypass, increased the expression of CYP 2R1 ( 142 ).…”
Section: Ir a Determinant Of Deficit Of Vitamin Dsupporting
confidence: 61%
“…Although the 25-hydroxylation is classically thought to be poorly regulated, Bell et al reported that hepatic 25-hydroxylation was inhibited by 1,25(OH) 2 D and parathyroid hormone (PTH) in humans [ 26 ]. Furthermore, several recent studies have described the inhibition of Cyp2r1 mRNA levels and/or 25-hydroxylation activity in the liver of obese/diabetic mice [ 27 , 28 , 29 , 30 , 31 ] via mechanisms involving several transcription factors including PGC1α and GR [ 31 ]. The 25(OH)D thus produced is the major circulating form of VD, with a half-life of about 15 days, and is classically used as a biomarker of VD status [ 32 ].…”
Section: Metabolism Of the Vitamin Dmentioning
confidence: 99%
“…The liver is the major site expressing Cyp2r1 ; however, our previous studies have shown that Cyp2r1 is expressed also in extrahepatic tissues ( 11 ). Therefore, we analyzed Cyp2r1 expression in some extrahepatic tissues [ie, kidney, brown adipose tissue (BAT), and testis] of the nondiabetic and diabetic mice from the 13-week experiment.…”
Section: Resultsmentioning
confidence: 99%
“…We previously demonstrated that CYP2R1 expression was suppressed in the mouse liver by fasting, high-fat diet (HFD)-induced obesity and streptozotocin (STZ)-induced diabetes ( 10 ). Furthermore, in the obese mice, the plasma 25-OH-D level was reduced, and in the livers of fasting mice, the vitamin D 25-hydroxylase activity was strongly reduced ( 10 , 11 ) Moreover, Roizen et al reported that livers of the HFD-fed, obese mice had reduced vitamin D 25-hydroxylase activity ( 12 ). These data thus support the notion that downregulation of CYP2R1 expression associates with reduced vitamin D 25-hydroxylase activity and could at least partially explain why the vitamin D deficiency is commonly associated with obesity and diabetes.…”
mentioning
confidence: 99%